CONCEPTUAL BASIS OF THE DEVELOPMENT OF ENTERPRISE'S EXPORT POTENTIAL - KHACHATRYAN, Valentyna; STRATIICHUK, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article carries out a comparative analysis of the essence of the enterprise's export potential. The main approaches of scientists regarding the interpretation of this concept highlighted. The conceptual bases of the interpretation of the export potential substantiated. The main approaches to the interpretation of the essence of export potential highlighted, in particular, resource, and market, effective, system-structural. Taking into account the definitions of scientists, it proposed to consolidate the essential characteristics of the concepts of "export potential" from the point of view of various approaches. It proposed to define export potential as a component of the overall economic potential of the enterprise, which ensures the realization of its export capabilities using available production, labor, financial, innovative and other type resources necessary for the formation of competitive advantages of the enterprise on the international market. An analysis of the classification of the enterprise's export potential was carried out, based on which an improved classification of the enterprise's export potential was proposed.
Keywords: export; export potential; export activity; international activity